Isokinetic force-power profile of the shoulder joint in males participating in CrossFit training and competing at different levels - Torres Banduc, Maximiliano Andrés.; Jerez Mayorga, Daniel.; Moran, Jason; Keogh, Justin W. L.; Ramírez Campillo, Rodrigo. (PeerJ Inc., 2021)
As participants who engage in CrossFit training and competition perform a large volume of high intensity overhead activities, injuries to the shoulder are one of the most common in this sport. Previous research in other sports has indicated that the isokinetic force power profile of the shoulder joint (IPSJ) rotator muscles may assist in the prediction of shoulder injury.
Keywords: Execise therapy; Human physical conditioning; Injuries; Plyometric exercise; Resistance training; Strength training; Physical education and training; Sports; Athletic performance; Return to sport